On the fold thickness of some classes of graphs - Campena, Francis Joseph H. (Animo Repository, 2006)
A graph G0 obtained from G by identifying two non-adjacent vertices in G having a common neighbor is called a 1-fold of G. A sequence G0,G1,G2, . . . ,Gk of graphs such that G0 = G and Gi is a 1-fold of Gi1 for i = 1, 2, 3, . . . , k is a uniform k-folding of G if all the graphs in the sequence are singular or all are non-singular. The fold thickness of a graph G is the largest integer k for which there is a uniform k-folding of G. It is known that the fold thickness of a bipartite graph of order n is n 3 if it is singular and 0 otherwise. We will show here formulas for the fold thickness of the cartesian product of some graphs.